The Effect The Effect of Education Level, Human Relations, and Job Description on the Performance of PMD Office Employees of Buleleng Regency - Ni Made Widnyani; I Putu Agus Adnyana; Kadek Desi Ariani Desi (ARTHA SATYA DHARMA, 2023)
Management is a process for using human resources to achieve goals. Organizations without management are impossible to achieve the desired goals effectively and efficiently. Human resources are an important component in the world of work, especially in the increasingly advanced modern era. Human resources serve as planners, performers, and determinants of achieving organizational goals. The purpose of this study was to determine the effect of Education Level, Human relations, and Job Description on the Performance of PMD Office Employees of Buleleng Regency. The technical analysis used in this study is validity and reality test, classical assumption test, multiple linear regression analysis test, determination analysis and t-test. The results showed that the level of education, human relations, and Job Description affect the performance of PMD Office employees of Buleleng Regency. This result is proven by testing the hypothesis with the T-Test, each of which obtained that t-count > t-table (3.252 > 1.67793) with value (a = 5%) = 0.002 below 0.05 then the hypothesis is accepted by t-count > t-table (3.596> 1.67793) with probability) value (a= 5%) = 0.001 below 0.05 then the hypothesis is accepted and the t-count value > t-table (1.994 > 1.67793) with probability value (a= 5%) = 0.049 below 0.05 then the hypothesis is accepted. The results of this study show a positive influence on the Level of Education, Human relations and Job Description on the Performance of PMD Office Employees of Buleleng Regency.